Subclinical Hypothyroidism as an overlooked contributor to depression and mood disorders - Cieplak, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction and Purpose: Thyroid hormones regulate metabolism and brain function, including mood and cognition. Subclinical hypothyroidism (SCH), defined by elevated TSH with normal fT3 and fT4, often goes unnoticed due to vague symptoms. This review investigates the possible link between SCH and mood disorders, particularly depression, and outlines potential neurobiological mechanisms. Materials and Methods: A narrative review of the literature was conducted using clinical trials, meta-analyses, and epidemiological data. The focus was on studies assessing the psychiatric impact of SCH and the effects of levothyroxine (L-T4) treatment on depressive symptoms in these patients. State of Knowledge: Evidence suggests that individuals with SCH—especially women and older adults—may experience increased depressive symptoms, fatigue, and cognitive impairment. Proposed mechanisms include disrupted serotonin and dopamine pathways, reduced neurotrophic factors, and HPT axis dysregulation. While some studies report benefits from L-T4 therapy, others find no significant effect, indicating the need for personalized treatment decisions. Conclusion: SCH may contribute to mood disorders, though a causal relationship remains unconfirmed. Thyroid function assessment should be considered in patients with unexplained depression. Personalized therapy and interdisciplinary collaboration are key, and more large-scale research is needed.